Overexpression of MicroRNA-16 Alleviates Atherosclerosis by Inhibition of Inflammatory Pathways. (21st July 2020) - Wang, Manman; Li, Jiao; Cai, Jiageng; Cheng, Lijun; Wang, Xuewen; Xu, Pengjuan; Li, Guangping; Liang, Xue
Abstract : Background . Our previous study demonstrated that the expression of miR-16 was downregulated in the cell and animal models of atherosclerosis (AS), a main contributor to coronary artery disease (CAD). Overexpression of miR-16 inhibited the formation of foam cells by exerting anti-inflammatory roles. These findings indicated miR-16 may be an anti-atherogenic and CAD miRNA. The goal of this study was to further validate the expression of miR-16 in CAD patients and explore its therapeutic roles in an AS animal model. Methods . A total of 40 CAD patients and 40 non-CAD people were prospectively registered in our study. The AS model was established in ApoE-/- mice fed a high-fat diet. The model mice were randomly treated with miR-16 agomiR (n = 10 ) or miR-negative control (n = 10 ). Hematoxylin-eosin staining was conducted for histopathological examination in thoracic aorta samples. ELISA and immunohistochemistry were performed to determine the expression levels of inflammatory factors (IL-6, TNF- α, MCP-1, IL-1 β, IL-10, and TGF- β ). qRT-PCR and western blotting were carried out to detect the mRNA and protein expression levels of PDCD4, miR-16, and mitogen-activated protein kinase pathway-related genes. Results . Compared with the normal control, miR-16 was downregulated in the plasma and peripheral blood mononuclear cell of CAD patients, and its expression level was negatively associated with IL-6 and the severity of CAD evaluated by the Gensini score, but positively related with IL-10. Injection of miR-16 agomiR in ApoE-/- mice reduced the formation of atherosclerotic plaque and suppressed the accumulation of proinflammatory factors (IL-6, TNF- α, MCP-1, and IL-1 β ) in the plasma and tissues but promoted the secretion of anti-inflammatory factors (IL-10 and TGF- β ). Mechanism analysis showed overexpression of miR-16 might downregulate target mRNA PDCD4 and then activate p38 and ERK1/2, but inactivate the JNK pathway. Conclusions . Our findings suggest miR-16 may be a potential diagnostic biomarker and therapeutic target for atherosclerotic CAD.